Evidence-Based Management in U.S. Academic and pre-NARA Presidential Libraries - Rudasill, Lynne M.; Dole, Wanda V. (Qualitative and Quantitative Methods in Libraries; Vol 6 No 3 (2017): September 2017 Issue, 2019)
Tools to support good decision-making in times of disappearing resources are abundant. Technology has challenged libraries to adapt to a new landscape in providing services to their populations. What tools are being employed by administrators to discover useful data for library administration? Even more important, are the data being developed in the process of evaluation used to support decision-making? Are the same tools and techniques viable for all types of libraries? Although there are established tools and techniques for U.S. academic libraries, there are few for presidential libraries, especially those which are not part of the federal National Archives and Records Administration (NARA) system. In this paper, the management data used by academic and presidential libraries are explored to discover common applications.